Women preference towards purchasing fashion and beauty products through e-Commerce in Selangor / Abdul Arif Abdul Ghafar, Ainun Nadzirah Mahmood and Zubaidah Zahiruddin - Abdul Ghafar, Abdul Arif; Mahmood, Ainun Nadzirah; Zahiruddin, Zubaidah (Faculty of Business and Management, 2023)
Substantial rise in internet access and e-Commerce is a tendency for people to purchase online. Malaysia has become one of the fastest growing in emerging e- commerce markets in Southeast Asia. With the emergence of big e-commerce firms, this somehow reflects that Malaysian women consumers are quite inclined to buy fashions and beauty products through the e-commerce. According to Internet User Survey Report 2017 by Malaysian Communication and Multimedia Commission (MCMC), purchasing online has become an important activity for internet user in Malaysia. Realizing this, the e-commerce organization need to identify what are the women preference towards purchasing fashion and beauty products through e-commerce in Selangor. This study is conducted to determine the factors that influence the preference of woman to purchase fashion and beauty products through e-commerce in Selangor. The factors that influence the preference of woman to purchase fashion and beauty products in Malaysia through ecommerce were studied. The findings of this paper will benefit the online retailer, e- commerce organization and also to the e-commerce user in in Selangor.